International markets entry strategy determinants: an exploratory study in Peru - Robles Gutiérrez, Fernando (2017)
Nowadays a progressively more dynamic and global economic environment causes a higher number of enterprises to pick an entry strategy to become international. The choice of a strategy of entry into foreign markets constitutes one of the most relevant decisions for a company, for it impacts on its performance and means it being ready to cooperate, to a greater or lesser extent, with global supply chains. The present article identifies the determining factors of the strategies of entry into international markets as implemented by Peruvian businessmen, which impact on the integration level into an international market. The companies that participated in this exploratory study have growing exportation levels within the non-traditional sector. The results allow to appreciate exporters employing entry strategies with low levels of integration, and predominantly prefer low-risk markets and high resemblance to the Peruvian market, with regards to cultural affinity and business behavior.